Climate and Disaster Resilience in Cities. - Shaw, Rajib (Community, Environment and Disaster Risk Management, 6., 2011)
This is the first book to combine academic research and field practice on urban risk reduction, specifically on the climate-related disasters in Asia. Regional, national, city and community-based studies examine issues of resilience and look at how to enhance actions at local levels and implement plans through multi-stakeholder collaboration.